Efficacy and safety in clinical practice of a rilpivirine, tenofovir and emtricitabine single‐tablet regimen in virologically suppressed HIV‐positive patients on stable antiretroviral therapy. Issue 1 (30th July 2015) - Gianotti, Nicola; Poli, Andrea; Nozza, Silvia; Spagnuolo, Vincenzo; Tambussi, Giuseppe; Bossolasco, Simona; Cinque, Paola; Maillard, Myriam; Cernuschi, Massimo; Galli, Laura; Lazzarin, Adriano; Castagna, Antonella
Abstract : Introduction: Switching to a rilpivirine, tenofovir and emtricitabine (RTE) single‐tablet regimen (STR) has been evaluated in a limited number of virologically suppressed patients. The aim of this study was to describe clinical outcomes in HIV‐positive patients switched from a suppressive antiretroviral regimen to RTE STR in routine clinical practice. Methods: In this retrospective study of antiretroviral‐treated patients with <50 copies of HIV RNA/mL switched to RTE STR, virological failure (VF) was defined as two consecutive measurements of ≥50 copies/mL or a single measurement of ≥50 copies/mL followed by any change in treatment. Treatment failure (TF) was defined as VF or discontinuation of the STR for any reason. Univariate mixed‐linear models were used to identify differences in laboratory parameters over time. Results and discussion: The analysis involved 307 patients (83% males) with a median age of 45.8 years (interquartile range (IQR 39.3–50.9), who were followed up for a median of 7.4 months (IQR 4.6–10.9). VF occurred in three patients (1%) switched from a protease inhibitor (PI)‐based regimen, after a median of 2.6 months (IQR 1.6–3.0), and TF in 34 patients (11%) after a median of three months (IQR 1.4–5.8), 24 of whom (71%) were receiving a PI‐based regimen at baseline. Overall, there was a slight but statistically significant improvement in the mean monthly change from baseline in CD4+ cell counts ( p =0.027), the CD4+/CD8+ ratio ( p =0.0001), and Hb ( p =0.024), alanine amino transferase (ALT) ( p =0.009), total bilirubin ( p <0.0001), indirect bilirubin ( p <0.0001), total cholesterol ( p <0.0001) and triglyceride ( p <0.0001) levels. There was also a slight but statistically significant increase in serum creatinine ( p =0.0004), aspartate amino transferase (AST) ( p =0.001) and liver fibrosis index (FIB‐4) ( p =0.002), and a decrease in eGFRcreat ( p <0.0001) and high‐density lipoprotein (HDL) cholesterol ( p <0.0001) values. The study limitations include its retrospective design, the relatively short follow‐up, and the absence of data concerning the severity of clinical adverse events; however, it does provide new information concerning the laboratory changes that occur in patients switching from PI‐based or PI‐sparing regimens to RTE STR. Conclusions: The study findings confirm the efficacy and safety in clinical practice of switching to RTE STR in virologically suppressed patients receiving other antiretrovirals.